The justice motive in adolescence and young adulthood : origins and consequences - Dalbert, Claudia; Sallay, Hedvig (Routledge research international series in social psychology, 2004)
This book is an overview of the development of justice related beliefs in different socialisation contexts and also of the role this plays in protecting mental health and promoting career development for adolescents and young adults.